(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, in the development of the national methodology for evaluating the effectiveness of the use of investments in the development of small business and private entrepreneurship, universal analytical approaches that are specific to the country’s economy and can reflect the general characteristics of various sectors and branches of the republic’s economy are reflected. It is recommended to divide the factors affecting the efficiency of investment activity of small business and private business entities into different groups based on the degree of mutual relationship.